Some Solutions to Attract Potential Tourists to Vietnam - A Promising Destination - Hoi, Huynh Tan (The journal of contemporary issues in business and government, 2021)
In today's era, tourism has not only become a popular phenomenon, but also become a spearhead economic sector, as well as bringing huge financial resources to many countries, regions and territories around the world in which have Vietnam. Not only that, but tourism also creates many jobs, promotes the development of service industries in general, develops infrastructure and is also a means of promoting peace, cultural exchange; thereby creating intangible but durable values. Vietnam is a promising land with tourism traditions that are always associated with natural destinations, beaches, historical and cultural relics. Therefore, it is very important to focus on building and developing tourism destinations, at the same time building the right strategies suitable for each specific destination, contributing to development of the country. The paper is completed by analyzing and comparing the data of recent and previous research paper. The results show that Vietnam needs to have more practical solutions to make tourism industry much stronger.